The association of cumulative psychosocial risk on child social-emotional symptoms at the age of 5 years – early childhood temperament as a moderating factor - Vizavitin-Uitamo, Sofia (My University, 2025)
Cumulative psychosocial risk has been linked to problems in child social-emotional development. However, child temperament traits may operate as resilience factors protecting child from adverse social-emotional outcomes. Yet, only limited number of studies have examined child temperament traits as moderators in the presence of cumulative risk exposure. To fill this gap, the present study examined the associations between early cumulative psychosocial risk and child social-emotional symptoms, as well as whether these associations are moderated by child temperament traits. In addition, this study examined the associations between child temperament traits and child social-emotional symptoms. The present study included 464 children from the population-based FinnBrain Birth Cohort study. The early cumulative psychosocial risk score included seven risk factors collected from both parents between gestational week 14 and child being 5 years old. The risk factors measured parental psychological symptoms, relationship quality and socioeconomic status. In addition, mothers completed self-report questionnaires on child temperament traits using Early Childhood Behavior Questionnaire (ECBQ) at 2 years and child social-emotional symptoms using Strengths and Difficulties Questionnaire (SDQ) at 5 years. Using general linear multiple analyses (GLM) the results revealed a positive association between cumulative psychosocial risk and all child social-emotional symptoms. Further, higher effortful control was associated with lower level of all child social-emotional symptoms. Higher surgency was associated with higher level of conduct problems and hyperactivity/inattention symptoms and fewer peer relationship problems but was not associated with emotional symptoms. Finally, surgency and effortful control did not moderate the association between cumulative psychosocial risk and any child social-emotional symptoms. The findings of this study highlight the detrimental effects of early cumulative risk on child social-emotional development. Finally, it is important for future studies to further examine temperament traits as protective factors on the association between cumulative risk and child social-emotional symptoms for example by including different subpopulations, age groups and measures of temperament.

Kumulatiivisen psykososiaalisen riskin on havaittu olevan yhteydessä lapsen sosioemotionaalisen kehityksen vaikeuksiin. Lapsen temperamenttipiirteet saattavat kuitenkin suojata lasta sosioemotionaalisten oireiden syntymiseltä. Tästä huolimatta vain pieni määrä tutkimuksia on tarkastellut lapsen temperamenttipiirteiden suojaavia vaikutuksia kumulatiivisen riskin yhteydessä. Tämä tutkimus tarkasteli kumulatiivisen psykososiaalisen riskin yhteyttä lapsen sosioemotionaalisiin oireisiin sekä moderoiko lapsen temperamentti tätä yhteyttä. Lisäksi tämä tutkimus tarkasteli lapsen temperamenttipiirteiden ja lapsen sosioemotionaalisten oireiden yhteyksiä. Tämän tutkimuksen otos koostui 464 lapsesta, jotka olivat osa FinnBrain-kohorttitutkimuksen aineistoa. Kumulatiivinen psykososiaalinen riski sisälsi seitsemän molemmilta vanhemmilta mitattua riskimuuttujaa, jotka kerättiin raskausviikon 14 ja lapsen ollessa 5-vuotias välillä. Riskimuuttujat mittasivat vanhempien psyykkistä oireilua, parisuhteen laatua ja sosioekonomista asemaa. Lisäksi äidit täyttivät itsearviointikyselyitä lapsen temperamenttipiirteistä käyttäen ECBQ-kyselylomaketta lapsen ollessa 2-vuotias ja lapsen sosioemotionaalisista oireista käyttäen SDQ-kyselylomaketta lapsen ollessa 5-vuotias. Yleisiä lineaarisia malleja käytettiin tutkimaan muuttujien välisiä yhteyksiä. Kumulatiivinen riski oli positiivisesti yhteydessä kaikkiin lapsen sosioemotionaalisiin oireisiin. Temperamenttipiirteistä korkeampi tahdonalainen itsesäätely oli yhteydessä pienempään määrään kaikkia lapsen sosioemotionaalisia oireita. Korkeampi ulospäinsuuntautuneisuus oli yhteydessä suurempaan määrään käytösoireita sekä yliaktiivisuus-/keskittymisvaikeuksia ja pienempään määrään vertaissuhdeongelmia, mutta ei ollut yhteydessä emotionaalisiin oireisiin. Ulospäinsuuntautuneisuus ja itsesäätely eivät moderoineet kumulatiivisen psykososiaalisen riskin ja lapsen sosioemotionaalisten oireiden välistä yhteyttä. Tämä tutkimus osoittaa, että varhaisella kumulatiivisella riskillä on haitallisia vaikutuksia lapsen sosioemotionaaliselle kehitykselle. Tulevaisuudessa olisi tärkeää tutkia lisää temperamenttipiirteiden mahdollisia suojaavia vaikutuksia kumulatiivisen riskin ja lapsen sosioemotionaalisten oireiden väliselle yhteydelle huomoioimalla esimerkiksi erilaisten alaryhmien, ikäryhmien ja temperamentin mittareiden vaikutukset tuloksiin.
Keywords: cumulative risk, parental well-being, socioeconomic status, temperament, social-emotional development, preschool age, kumulatiivinen riski, vanhemman hyvinvointi, sosioekonominen asema, temperamentti, sosioemotionaalinen kehitys, esikouluikä